1998
DOI: 10.1073/pnas.95.20.11733
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between notochord and floor plate in vertebrate development revisited

Abstract: The relationships between notochord and floor plate in vertebrate development revisited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 39 publications
5
64
1
1
Order By: Relevance
“…Cells in the embryonic shield of zebrafish embryos, similar to cells in Hensen's node in chicken, can contribute to both notochord and floor plate (Woo and Fraser, 1995;Catala et al, 1996;Teillet et al, 1998). Floor plate-specific gene expression already commences in the embryonic shield (Ekker et al, 1995), indicating that floor plate specification is well under way before the notochord has formed a discrete entity.…”
Section: Introductionmentioning
confidence: 99%
“…Cells in the embryonic shield of zebrafish embryos, similar to cells in Hensen's node in chicken, can contribute to both notochord and floor plate (Woo and Fraser, 1995;Catala et al, 1996;Teillet et al, 1998). Floor plate-specific gene expression already commences in the embryonic shield (Ekker et al, 1995), indicating that floor plate specification is well under way before the notochord has formed a discrete entity.…”
Section: Introductionmentioning
confidence: 99%
“…During embryo elongation, MPCs continuously join growing tissues of the midline. In chicken embryos it is clear that different germ layer derivatives form from a single pool of MPCs, whereas in mouse embryos the notochord and floor plate progenitors are spatially distinct (Catala et al, 1996;Jeong and Epstein, 2003;Teillet et al, 1998). Whether MPC fate decisions are made solely during gastrulation or continuously during embryo elongation after gastrulation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The delay of apparition of the Shh transcripts in the floor plate compared to the underlying notochord provided one of the principal arguments in favor of the hypothesis of the floor plate induction by the notochord (Dodd et al, 1998;Tanabe and Jessell, 1996). However, although it is possible to induce experimentally a supplementary floor plate by the action of a notochord (see another section of this paper), we have demonstrated that the prolonged presence of the notochord under the floor plate territory is not necessary for its differentiation (Teillet et al, 1998a). …”
mentioning
confidence: 84%
“…This chick neural tube with quail midline cells was back-grafted into a stage-matched chick embryo in the absence of notochord. A normal floor plate differentiated in the region where quail midline cells were present showing that self-differentiation of MFP can occur (Teillet et al, 1998a). Moreover it should be noticed that in embryos in which the node was only partly excised (Charrier et al, 1999), the floor plate alone differentiates in the lumbar region without an underlying notochord.…”
Section: Floor Plate Development Can Occur Independently Of the Notocmentioning
confidence: 99%
See 1 more Smart Citation